PENERAPAN TEKNOLOGI PEMBUATAN SABUN AROMA TERAPI DARI MINYAK KELAPA PADA KWT “WIGUNA MEKAR” DI DESA ANGKAH KECAMATAN SELEMADEG BARAT KABUPATEN TABANAN - Ganda-Putra, G.P.; Wartini, N.M.; Wrasiati, L.P.; Yoga, I.W.G.S. (Buletin Udayana Mengabdi, 2018)
People in the Angkah village, District of West Selemadeg in Tabanan Regency, especially members of the KWT "Wiguna Mekar" still do not understand the process of making aromatherapy soap. This causes not yet exploited coconut oil that are produced in the area. The purpose community service activities are: (1) providing information about the process of making aromatherapy soap is made from coconut oil and (2) provide training and practice on the steps of the process of making aroma therapy soap is made from coconut oil, as well as the evaluation of the cost of production and sensory quality of the product. Results of activity show that: 1) education about aromatherapy soap making from the material coconut oil has provided the information and knowledge required by KWT Wiguna Mekar, 2) training of aromatherapy soap making made from coconut oil can be done either by the participants, 3) result a sensory test of aromatherapy soap products, each with a score of: color = 6.5 (like - really like), aroma = 6.3 (like - really like), foaming = 5.8 (rather like - likes), and clean (rough impression) = 6.1 (like - really like), and 4) from the weight of 500 grams of raw materials will be produced 20 pieces of soap, with a total cost of Rp.25.500,- or costs of Rp. 1.275,- for one pieces of soap.